2022
DOI: 10.3390/healthcare10122407
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Blood Flow Restriction in Neurological Disorders: A Systematic Review

Abstract: There is scientific evidence that Blood Flow Restriction (BFR) is beneficial in healthy people, the elderly and patients with musculoskeletal disorders. A systematic review was conducted to evaluate the effectiveness of BFR in patients with neurological disorders. The literature search was conducted up until July 2022 in the following databases: PubMed, Web of Science (WOS), Physiotherapy Evidence Database (PEDro), LILACS, Scopus, Cumulative Index of Nursing and Allied Literature Complete (CINAHL), the Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Currently, it has been analyzed whether BFR intervention is capable of directly influencing other variables such as pain, functionality, and quality of life, obtaining favorable results that indicate that this technique can improve, above all, the intensity of pain and the ability to perform activities of daily living [12]. Although there are many systematic reviews that analyze the effect of BFR intervention [3,[13][14][15][16][17][18][19][20][21], no systematic review has been found that analyzes the effect of BFR intervention on subjective and objective variables in the short-, medium-, and long-term in patients suffering from neuromusculoskeletal pathologies. Thus, to date, and to the best of our knowledge, no review has analyzed how BFR intervention can directly contribute to these variables in the rehabilitation area.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it has been analyzed whether BFR intervention is capable of directly influencing other variables such as pain, functionality, and quality of life, obtaining favorable results that indicate that this technique can improve, above all, the intensity of pain and the ability to perform activities of daily living [12]. Although there are many systematic reviews that analyze the effect of BFR intervention [3,[13][14][15][16][17][18][19][20][21], no systematic review has been found that analyzes the effect of BFR intervention on subjective and objective variables in the short-, medium-, and long-term in patients suffering from neuromusculoskeletal pathologies. Thus, to date, and to the best of our knowledge, no review has analyzed how BFR intervention can directly contribute to these variables in the rehabilitation area.…”
Section: Introductionmentioning
confidence: 99%